Bolagsstämmans bundenhet av vinstsyftet – Erkända avsteg och hållbar bolagsstyrning som möjlig undantagsgrund - Påhlman,Joel (2025)
Within the framework of the overall debate on sustainable development, the profit motive under company law has been called into question. Critics argue that the profit requirement presumed by law risks leading companies to ne-glect sustainability work in favour of profit maximisation. This risk has been recognised in English legislation, which, with the entry into force of the Com-panies Act 2006, stipulates that directors must take certain sustainability inter-ests into regard in their work, alongside the interests of the company. The purpose of this thesis is to investigate which exceptions to the general meet-ing’s commitment to the profit motive are recognised in Swedish law, to ana-lyse the motives behind these exceptions, and to examine the extent to which sustainable corporate governance can constitute an additional exception to the profit motive, both at present and in the future. Within the framework of the purpose, legal developments and the legal situation in Sweden are compared with those in England. The essay begins with an account of the emergence of the limited company (aktiebolag) and the Swedish Companies Act (ABL). The historical back-ground is followed by an account of the current role of the profit motive in company law and the most important functions of the principle. This is fol-lowed by an analysis of the exceptions to the profit motive in Swedish law, such as exceptions under the SAS-principle and exceptions in the event of liquidation. The presentation of the recognised exceptions is followed by an account of the debate and legal situation surrounding sustainable corporate governance as a basis for exceptions to the profit motive. The investigative part of the thesis concludes with a comparative account of English law, pre-senting the main features of company law and the relationship between the profit motive and sustainable corporate governance. The thesis concludes that the currently recognised exceptions to the binding nature of the profit motive in Swedish law are the result of a balancing of dif-ferent interests, where the functions of the profit motive have been subordi-nated to a more pressing need. However, the functions of the profit motive are satisfied as far as possible by other protective provisions, such as the general clause in 7 kap. 47 § or the voting thresholds in kap. 7 ABL, which come into force when deviations from the profit motive are made. Sustainable corporate governance cannot be considered grounds for an exception to the general meeting’s commitment to the profit motive in the current legal situation, but this result must be viewed in light of the fact that most sustainability work can be justified from a business strategy perspective and thus falls within the scope of the profit motive. Finally, it is noted that there are several alternatives for introducing an exception for sustainable corporate governance, and that guidance for this could be drawn from English law. However, there is reason to be critical of a reform of the profit motive, and such a reform is unlikely to be expected in the near future.
Keywords: associationsrätt; förmögenhetsrätt; komparativ rätt; comparative law; rättsvetenskap; law; ABL; vinstsyfte; vinstsyftet; hållbarhet; bolagsstyrning; hållbar bolagsstyrning; Companies Act; company law; aktiebolagsrätt; aktiebolagslagen; bolag; bolagsrätt